Pengaruh Penggunaan Shopee Paylater Dan Motivasi Pelanggan Terhadap Keputusan Pembelian Pada Aplikasi Shopee Pada Mahasiswa Bisnis Digital Unismuh Luwuk - Riski Lamato; Sigit Sugiarto; Andi Siti Raodahtuljannah (LPPM STIEM BONGAYA, 2026)
This study aims to analyze the effect of Shopee PayLater usage and customer motivation on purchasing decisions among students of the Digital Business Study Program at Muhammadiyah University of Luwuk who use the Shopee application. This research employed a quantitative descriptive approach with a sample of 30 respondents selected using the snowball sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression analysis, t-test, F-test, and the coefficient of determination (R²) with the assistance of SPSS software. The results indicate that Shopee PayLater usage has a positive and significant effect on purchasing decisions (t-value = 3.272; sig. = 0.003), while customer motivation has no significant effect on purchasing decisions (t-value = 0.636; sig. = 0.530). Simultaneously, Shopee PayLater usage and customer motivation have a positive and significant effect on purchasing decisions (F-value = 12.179; sig. = 0.000). These findings suggest that the use of Shopee PayLater is a key factor in encouraging purchasing decisions, whereas customer motivation does not have a significant individual effect. However, both variables collectively contribute to improving purchasing decisions on the Shopee application